Pharmacological Mechanisms and Adjuvant Properties of Licorice Glycyrrhiza in Treating Gastric Cancer - Joanna Japhet Tibenda; Yuhua Du; Shicong Huang; Guoqing Chen; Na Ning; Wenjing Liu; Mengyi Ye; Yi Nan; Ling Yuan (Molecules, 2023)
Licorice is a remarkable traditional Chinese medicine obtained from the dried root and rhizomes of the Glycyrrhiza genus, and t has been utilized in China for many centuries. It consists of more than 300 compounds that are mainly divided into triterpene saponins, flavonoids, polysaccharides, and phenolic components. The active compounds of licorice have been found to possess multiple biological activities, including antitumor, anti-inflammatory, antiviral, antimicrobial, immunoregulatory, cardioprotective, and neuroprotective functions. In addition to providing a brief overview of licorice’s adjuvant properties, this review describes and analyzes the pharmacological mechanisms by which licorice components function to treat gastric cancer. Furthermore, licorice compounds are also found to be potent adjuvant chemotherapy agents, as they can improve the quality of life of cancer patients and alleviate chemotherapy-induced adverse effects.